Resident Attitudes Toward Timber Rattlesnakes (Crotalus horridus). Issue 9 (1st September 2020) - Keener-Eck, Lindsay S.; Morzillo, Anita T.; Christoffel, Rebecca A.
Abstract: Timber rattlesnakes ( Crotalus horridus ) are endangered throughout the northeastern United States where multiple factors contribute to population declines. Challenges exist to managing rattlesnake populations because there is little information about human dimensions of this species or other small predators that are venomous or perceived as hazardous. Our objective was to evaluate relationships between resident attitudes and behavioral intentions toward timber rattlesnakes. A mail survey ( n  = 593) was used to collect data from residents who live near a rattlesnake population in central Connecticut. Two variables defined resident attitudes toward rattlesnakes: coexistence with the species and perceived threats from the species. Rattlesnake-related factors and situational factors appeared to contribute more heavily to behavioral intentions toward rattlesnakes than general wildlife value orientations. Attitudes predicted behavioral intentions toward rattlesnakes. Results will help wildlife managers incorporate human factors into appropriate management and public outreach strategies.